Agronomic efficiency and genome mining analysis of the wheat-biostimulant rhizospheric bacterium Pseudomonas pergaminensis sp. nov. strain 1008T - Díaz, Marisa; Bach, Teresa; González Anta, Gustavo; Agaras, Betina; Wibberg, Daniel; Noguera, Fabián; Canciani, Wilter; Valverde, Claudio (Frontiers in Plant Science, 2022)
Pseudomonas sp. strain 1008 was isolated from the rhizosphere of field grown wheat plants at the tillering stage in an agricultural plot near Pergamino city, Argentina. Based on its in vitro phosphate solubilizing capacity and the production of IAA, strain 1008 was formulated as an inoculant for bacterization of wheat seeds and subjected to multiple field assays within the period 2010-2017. Pseudomonas sp. strain 1008 showed a robust positive impact on the grain yield (+8% on average) across a number of campaigns, soil properties, seed genotypes, and with no significant influence of the simultaneous seed treatment with a fungicide, strongly supporting the use of this biostimulant bacterium as an agricultural input for promoting the yield of wheat. Full genome sequencing revealed that strain 1008 has the capacity to access a number of sources of inorganic and organic phosphorus, to compete for iron scavenging, to produce auxin, 2,3-butanediol and acetoin, and to metabolize GABA. Additionally, the genome of strain 1008 harbours several loci related to rhizosphere competitiveness, but it is devoid of biosynthetic gene clusters for production of typical secondary metabolites of biocontrol representatives of the Pseudomonas genus. Finally, the phylogenomic, phenotypic and chemotaxonomic comparative analysis of strain 1008 with related taxa strongly suggests that this wheat rhizospheric biostimulant isolate is a representative of a novel species within the genus Pseudomonas, for which the name Pseudomonas pergaminensis sp. nov. (type strain 1008T=DSM 113453T=ATCC TSD-287T) is proposed.